2004
DOI: 10.1093/rpd/nch231
|View full text |Cite
|
Sign up to set email alerts
|

Personal neutron dosimetry in nuclear power plants using etched track and albedo thermoluminescence dosemeters

Abstract: Measurement of the personal dose equivalent rates for neutrons is a difficult task because available dosemeters do not provide the required energy response and sensitivity. Furthermore, the available wide calibration spectra recommended by the International Standard Organisation does not reproduce adequately the spectra encountered in practical situations of the nuclear industry. There is a real necessity to characterise the radiation field, in which workers can be exposed, and to calibrate personal dosemeters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 5 publications
0
2
0
1
Order By: Relevance
“…Il s'agit d'un convertisseur de 3 mm d'air, qui convertit les neutrons thermiques en protons par l'intermédiaire de la réaction 14 N (n, p) 14 C. Cette configuration (PADC0) a été exposée dans différents points du bâtiment réacteur de la centrale nucléaire de Vandellòs II (Fernández et al, 2004a) durant une campagne de caractérisation des spectres de neutrons avec notre système de spectrométrie neutronique par sphères de Bonner. L'étalonnage des dosimètres de routine est généralement fait en exposant ceuxci à des sources de neutrons de référence.…”
Section: Le Détecteur De Traces Cr-39 : Son Optimisation Comme Détectunclassified
“…Il s'agit d'un convertisseur de 3 mm d'air, qui convertit les neutrons thermiques en protons par l'intermédiaire de la réaction 14 N (n, p) 14 C. Cette configuration (PADC0) a été exposée dans différents points du bâtiment réacteur de la centrale nucléaire de Vandellòs II (Fernández et al, 2004a) durant une campagne de caractérisation des spectres de neutrons avec notre système de spectrométrie neutronique par sphères de Bonner. L'étalonnage des dosimètres de routine est généralement fait en exposant ceuxci à des sources de neutrons de référence.…”
Section: Le Détecteur De Traces Cr-39 : Son Optimisation Comme Détectunclassified
“…Different materials and methods has been studied and proposed to a efficient neutron dosimetry [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…These materials were exposed to either gamma, neutron or electron beam irradiation and their use as dosimeters for high and very high radiation dose analyzed [37,38,43,[54][55][56][57]. Neutron detection from a nuclear reactor or neutron sources (such as Am-Be or 252 Cf) using thermoluminescence detectors has been a great challenge in radiation dosimetry, and several works have been devoted to investigating this process in the past [58,[63][64][65][66][67][68][69]. Particularly, interaction of thermal and epithermal neutron with matter has awakened special interest in some authors because a larger effective neutron capture cross-section than fast neutrons is found for some nuclides like 10 B and 6 Li [70][71][72].…”
Section: High and Very-high Radiation Dosementioning
confidence: 99%